2012
DOI: 10.1002/art.34459
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional T cell reactivity with native and glycosylated type II collagen in rheumatoid arthritis

Abstract: Objective Type II collagen (CII) is a cartilage-specific protein to which a loss of immune tolerance may trigger autoimmune reactions and cause arthritis. The major T cell epitope on CII, aa259-273, can be presented by several HLA-DRB1*04 alleles in its native or posttranslational-glycosylated form. Here, we aimed to functionally explore and compare CII-autoreactive T cells from blood and synovial fluid of patients with rheumatoid arthritis (RA). Methods Peripheral blood were obtained from HLA-DRB1*04 RA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 24 publications
(8 reference statements)
3
48
1
Order By: Relevance
“…92 Furthermore, the presence of anti-carbamylated antibodies has been detected in serum samples collected before the onset of RA, 93 and emerging data in patients with established RA suggests that neutrophil extracellular trap (NET) formation are a source of citrullinated autoantigens in RA. 94 In addition, although emerging data is available regarding T-cell reactivity to specific citrullinated proteins and other antigens in patients with established RA, 95,96 no studies to date have directly evaluated the antigen specificity of T-cell and/or B-cell subsets during the preclinical stage of RA and compared this with the ACPA responses. Hope fully, well-designed prospective studies that methodically isolate and analyse peripheral blood mononuclear cells, including utilization of emerging technologies such as single-cell analyses that can identify antigen reactivity of specific immune cells, 97 will address this important question in the near future.…”
Section: Preclinical Studies In Ra and Slementioning
confidence: 99%
“…92 Furthermore, the presence of anti-carbamylated antibodies has been detected in serum samples collected before the onset of RA, 93 and emerging data in patients with established RA suggests that neutrophil extracellular trap (NET) formation are a source of citrullinated autoantigens in RA. 94 In addition, although emerging data is available regarding T-cell reactivity to specific citrullinated proteins and other antigens in patients with established RA, 95,96 no studies to date have directly evaluated the antigen specificity of T-cell and/or B-cell subsets during the preclinical stage of RA and compared this with the ACPA responses. Hope fully, well-designed prospective studies that methodically isolate and analyse peripheral blood mononuclear cells, including utilization of emerging technologies such as single-cell analyses that can identify antigen reactivity of specific immune cells, 97 will address this important question in the near future.…”
Section: Preclinical Studies In Ra and Slementioning
confidence: 99%
“…12 Previous reports have shown high numbers of activated CD4+ T cells in the inflamed joint. 13,14 Once activated, T lymphocytes stimulate macrophages and fibroblasts to secrete proinflammatory cytokines such as tumor necrosis factor (TNF), interleukin (IL)-1 and IL-6, as well as IL-17 and interferon (IFN)-g, 12,15 which constitute the key soluble factors in the inflammatory process of RA. However, no differences have been observed in IL-10 levels when RA patients are compared with healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The T cell responses in RA patients carrying HLA-DRB*04 alleles show a diverse pattern of CII259-273 epitope recognition, that is, toward both non-modified and glycosylated CII259-273; only few patients exclusively responded to K264 but most of them to GalOK264 [5,6]. A longitudinal analysis of CII-specific T cell responses showed a consistent reactivity but variable magnitude and specificity of the response over time [6].…”
Section: Discussionmentioning
confidence: 99%
“…We have identified a T cell immunodominant epitope from collagen type II (CII259-273) that plays a major role in CIA development in mice with H-2 q haplotype [10]. Subsequently, it was shown that this epitope also binds to human DR4 and DR1 molecules, associated with RA [11,12] and immunity to CII259-273 was detected also in RA patients [5,6,13]. Interestingly, the CII259-273 epitope could be posttranslationally modified (at position 264 and 270) by lysine hydroxylation and glycosylation.…”
Section: Introductionmentioning
confidence: 99%